Adding rooms onto a house we love: Central banking after the global financial crisis. (27th December 2018) - Johnson, Juliet; Arel‐Bundock, Vincent; Portniaguine, Vladislav
Abstract : This article examines the extent to which central bankers have been willing and able to rethink their beliefs about monetary policy in the wake of the global financial crisis. We show that despite the upheaval, the core pre‐crisis monetary policy paradigm remains relatively intact: central bankers believe that they should primarily pursue price stability through targeting a low inflation rate in a transparent manner, and that they need operational independence in order to achieve this goal. In a bid to address post‐crisis conditions and maintain their credibility, however, central bankers have also layered new elements onto this paradigmatic core. We document both the resilience of pre‐crisis beliefs and the process of layering using computer‐assisted text analysis and qualitative analysis of 13, 586 speeches given between 1997 and 2017 by central bankers from around the world.